The Child Seen as the Same or the Other? The Significance of the Social Convention to the Pedagogical Relation - Saevi, Tone; Husevaag, Heidi (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2009)
The aim of this article is to explore the lifeworld of children as they experience everyday conventional situations where proper behaviour is expected and to understand the significance of the social convention to the pedagogical relation between adult and child. Based on interviews with adults recalling pedagogical episodes of handshaking, waiting, and thanking someone, we describe and interpret narrative examples by the light of Continental phenomenological pedagogy. Including children in the traditions of a society by exposing them to situations where conventional behaviour and adherence to social norms are expected is an unavoidable ingredient of pedagogical practice. Adults often expect children to adapt to social conventions simply by being introduced to them, and at the same time as adults we are somehow prevented from seeing the meaning of the situation for the child by our grown-up-ness and the conventional quality of the situation. The socialization of children, including the transfer of conventionally proper behaviour from one generation to the next, introduces ethical and pedagogical dilemmas. We suggest that although social conventions of proper behaviour are desirable and important factors of socialization for the child, the social convention itself can be a pedagogical impasse that anticipates homogeneity and assimilation and renders difficult a pedagogically caring practice.